Reconstructing past seasonal to multi-centennial scale variability in the NE Atlantic Ocean using the long-lived marine bivalve mollusc Glycymeris glycymeris - Reynolds, DJ; Hall, IR; Slater, S; Scourse, JD; Halloran, PR; Sayer, MDJ (Paleoceanography, 2017)
This is the author accepted manuscript. The final version is available from AGU via the DOI in this record. The lack of long-term, highly resolved (annual to sub-annual) and absolutely dated baseline records of marine variability extending beyond the instrumental period (last ~50-100 years) hinders our ability to develop a comprehensive understanding of the role the ocean plays in the climate system. Specifically, without such records, it remains difficult to fully quantify the range of natural climate variability mediated by the ocean, and to robustly attribute recent changes to anthropogenic or natural drivers. Here we present a 211-year (1799-2010 CE; all dates hereafter are common era) seawater temperature (SWT) reconstruction from the northeast Atlantic Ocean derived from absolutely dated, annually resolved, oxygen isotope ratios recorded in the shell carbonate (δ18Oshell) of the long-lived marine bivalve mollusc Glycymeris glycymeris. The annual record was calibrated using sub-annually resolved δ18Oshell values drilled from multiple shells covering the instrumental period. Calibration verification statistics and spatial correlation analyses indicate that the δ18Oshell record contains significant skill at reconstructing Northeast Atlantic Ocean mean summer SWT variability associated with changes in sub-polar gyre (SPG) dynamics and the North Atlantic Current. Reconciling differences between the δ18Oshell data and corresponding growth increment width chronology demonstrates that 68% of the variability in G. glycymeris shell growth can be explained by the combined influence of biological productivity and SWT variability. These data suggest G. glycymeris can provide seasonal to multi-centennial absolutely dated baseline records of past marine variability that will lead to the development of a quantitative understanding of the role the marine environment plays in the global climate system. This work was supported by the NERC-funded CLAM project; (Project No. NE/N001176/1).